Transforming or reproducing conventional socioeconomic relations? Introducing a regulationist framework for the assessment of fairtrade - Staricco, Juan Ignacio (2017)
The certification-based Fair Trade initiative is usually described as an alternative form of organizing production, trade and consumption with the goal of advancing the situation of marginalized producers and workers. While much of the Fair Trade literature has analyzed the system's direct impacts on its beneficiaries, some strands have sought to determine its transformative potential vis-à-vis capitalist social relations. In an attempt to contribute to the latter debate, this paper introduces an analytical framework for the assessment of Fairtrade built on the basis of the French Regulation Approach. This perspective, which focuses on the specific ways in which Fairtrade structures and institutionalizes socioeconomic relations, seeks to examine this system from a holistic perspective, privileging the analysis of the qualitative changes it produces in economic institutions and structures. This article presents the main assumptions and concepts developed by the Regulation Approach and proposes a case-based research design that uses them to analyze how transformative Fairtrade proves to be and the impacts it produces on specific economic sectors. This methodological exposition is illustrated with examples from the case of Fairtrade wine produced in Argentina and consumed in the United Kingdom.